Probiotics - A Review - Kamala Kumari (Journal of Global Pharma Technology, 2021)
Probiotic bacteria are defined as live microorganisms that, when administered in adequate amounts, confer a health benefit on the host. While this beneficial effect was originally thought to stem from improvements in the intestinal microbial balance, there is now substantial evidence that probiotics can also provide benefits by modulating immune functions. Scientists continue to work on elucidation of the mechanisms of the most common probiotic strains. The results that might arise from could be extremely important because the use of probiotics to maintain health must be considered promising, although much remains to be elucidated. The universal use of some strains seems less reasonable from an ecological point of view than selection of strains from their natural habitat were they are adapted to the ecological niche. It is important to understand that all probiotic strains are unique and different and their properties and characteristics should be well defined.